Structure of the Mangrove Community in Batang Masang Beach Tiku V Jorong Tanjung Mutiara District Agam Regency West Sumatera - Syarif, Wilman; Nasution, Syafruddin; Mubarak, Mubarak (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
The survey was conducted in March 2021. The purpose of this survey was to analyze the structure of the mangrove community at Batang Masang Beach Nagari Tiku V Jorong Tanjung Mutiara District Agam Regency West Sumatra. The method used in this study is a survey method. In the mangrove area of ​​Batang Masang, 3 observation stations have been determined. Each observation station was drawn by 3 transects over 50 m drawn from the mangrove boundary of the sea to the land. In each transect, 3 plots were placed, each plot consisting of 3 sizes, namely 10 x 10 m for the tree category, 5 x 5 m for the sapling category, and 2 x 2 m for the seedling category. The results of the survey revealed that there were 2 classes, namely the Magnoliopsida class and the Liliopsida class. In the magnoliopsida class, there are 3 genera namely Acanthus, Rhizophora, and Sonneratia, and there are 3 species namely A. ilicifolius, R. apiculata, and S. alba. In the class Liliopsida there is only 1 genus, namely Nypa, and 1 species N. fruticans. Zone I is dominated by S. alba species, in zone II there are 2 dominant species, namely S. alba and R. Apiculata, and zone III is dominated by R.apiculata species. The criteria for mangrove vegetation are in the scarce criteria with densities ranging from 277.78 to 1066.67 ind/ha.